2021
DOI: 10.1186/s12885-021-09007-9
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life one year after the diagnosis of oesophageal cancer: a population-based study from the Swedish National Registry for Oesophageal and Gastric Cancer

Abstract: Background Population-based patient reported outcome data in oesophageal cancer are rare. The main purpose of this study was to describe health-related quality of life (HRQOL) 1 year after the diagnosis of oesophageal cancer, comparing subgroups of curatively and palliatively managed patients. Methods This is a nationwide population-based cohort study, based on the Swedish National Registry for Oesophageal and Gastric Cancer (NREV) with prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Individuals with esophageal squamous cell carcinoma (ESCC), worldwide the most common histological subtype of esophageal cancer, typically experience a severe symptom burden at diagnosis and associated reductions in health-related quality of life (HRQoL) due to esophageal obstruction throughout the course of their disease. 1 , 2 , 3 In addition, self-reported health status and ESCC-specific symptoms associated with HRQoL are predictive of overall survival (OS) in patients with potentially curable and advanced esophagogastric esophageal cancer, further underscoring the importance of these domains. 4 , 5 A better understanding of ESCC-specific symptoms, functioning, and associated HRQoL are especially needed for patients with advanced or metastatic ESCC given that second-line chemotherapy has limited efficacy with marginal antitumor activity, poor long-term survival, and significant toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with esophageal squamous cell carcinoma (ESCC), worldwide the most common histological subtype of esophageal cancer, typically experience a severe symptom burden at diagnosis and associated reductions in health-related quality of life (HRQoL) due to esophageal obstruction throughout the course of their disease. 1 , 2 , 3 In addition, self-reported health status and ESCC-specific symptoms associated with HRQoL are predictive of overall survival (OS) in patients with potentially curable and advanced esophagogastric esophageal cancer, further underscoring the importance of these domains. 4 , 5 A better understanding of ESCC-specific symptoms, functioning, and associated HRQoL are especially needed for patients with advanced or metastatic ESCC given that second-line chemotherapy has limited efficacy with marginal antitumor activity, poor long-term survival, and significant toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…The mean HRQoL score of physical and cognitive functioning was higher in esophageal cancer patients, suggesting good HRQoL in these domains. In contrast, studies in Sweden revealed that esophageal cancer patients had poor HRQoL in their physical functioning 30,39 . However, esophageal cancer patients had suboptimal HRQoL in the role, emotional, global health, and social domains of HRQoL that might be related to psychological distress due to the diagnosis of cancer and its treatment‐related adverse drug reactions and future uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies showed poor HRQoL in the symptom scales among esophageal cancer patients. 30,39,40 These variations could be the possibility of having better symptomatic management care in our setting as a national referral facility.…”
Section: Determinants Of Hrqol Among Gastrointestinal Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiopulmonary toxicity and fibrosis, although minimized with modern radiation techniques, is an evolving process over several months post-treatment. In long-term follow-up of NeoRes patients, chronic cough and persistent impairment in overall health-related QoL, even 5 years after surgery, were significantly more frequent after RCT [ 31 ]. In the present study, we also observed a trend to a higher length stay and of ICU stay.…”
Section: Discussionmentioning
confidence: 99%